Perancangan UI/UX Sistem Administrasi Surat Instansi Pemerintah Daerah Menggunakan Metode Design Thinking - Elvina Giovanni Amelinda; Dwi Hosanna Bangkalang (STMIK Banjarbaru, 2025)
The letter administration system plays a crucial role in supporting bureaucratic governance. However, the Forestry Service of UPT KPHP Mentaya Hulu - Seruyan Tengah still faces challenges such as delayed disposition, data duplication, and difficulties in tracking letters. Existing applications have not been fully effective since employees experience adaptation issues caused by suboptimal interface design and user experience. This study aims to design a UI/UX prototype for letter administration system that aligns with user needs, supports digitalization, and enhances management effectiveness. Development employed the Design Thinking method consisting of five stages: empathize, define, ideate, prototype, and test. System evaluation was conducted using the System Usability Scale (SUS) involving 26 respondents from various positions. The results showed an average score of 84.04 in the Excellent category, indicating the system is easy to use, understandable, and acceptable. These findings confirm that a user-centered design approach effectively improves administrative management in government institutions. Key Words: Design Thinking; UI/UX; System Usability Scale; Letter administration; Government institution AbstrakSistem administrasi surat berperan penting dalam mendukung tata kelola birokrasi. Namun, pada Dinas Kehutanan UPT KPHP Mentaya Hulu, Seruyan Tengah masih ditemukan hambatan berupa keterlambatan disposisi, duplikasi data, serta kesulitan pelacakan surat. Keberadaan aplikasi serupa belum optimal karena pegawai mengalami kendala adaptasi akibat rancangan antarmuka dan pengalaman pengguna UI/UX yang kurang sesuai. Penelitian ini bertujuan merancang prototype UI/UX sistem administrasi surat yang selaras dengan kebutuhan pengguna, mendukung proses digitalisasi, dan meningkatkan efektivitas pengelolaan surat. Pengembangan dilakukan dengan metode Design Thinking yang meliputi lima tahap, empathize, define, ideate, prototype, dan test. Evaluasi sistem menggunakan instrumen System Usability Scale (SUS) dengan melibatkan 26 responden dari berbagai jabatan. Hasil pengujian memperoleh skor rata-rata 84,04 pada kategori Excellent, yang menunjukkan rancangan mudah digunakan, dipahami, dan diterima. Temuan ini menegaskan bahwa pendekatan User-Centered Design efektif dalam meningkatkan kualitas pengelolaan administrasi surat di instansi pemerintah.Kata Kunci: Design Thinking; UI/UX; System Usability Scale; Administrasi surat; Instansi pemerintah